(untitled) (Altre Modernità, 2018)
This essay considers the figure of the author within collaborative writing for fiction. My discussion draws on two case studies from the late nineteenth century, a historical moment when literary collaboration witnessed its efflorescence: the collaborative experiences of the Anglo-Irish Edith Somerville with Martin Ross, and of the American Brander Matthews with his various male collaborators. The author-figure promoted in both Somerville’s and Matthews’s metadiscourses challenges and subverts established post-Romantic notions of authorship, according to which the author is a solitary, hypertrophic genius. As a matter of fact, due to the sharing of textual spaces and the dispersal of authorial ownership and control implied in coauthorship, the collaborative author fades away into a diluted, deliberately weakened, blurred and elusive figure: a ghost that, according to coauthors themselves, is – and must remain – concealed behind the text. I therefore suggest that the collaborative trend of the late Victorian period produced an embryonic dismantling of the author – though not systematically theorised and today largely unknown of.